PEMETAAN TINGKAT KERENTANAN TANAH LONGSOR DI DESA PANGU SATU DAN SEKITARNYA KECAMATAN RATAHAN TIMUR KABUPATEN MINAHASA TENGGARA PROVINSI SULAWESI UTARA - Alow, R.E.; Utomo, A.P. (Journal Geological Processes, Risks, and Integrated Spatial Modeling, 2024)
Southeast Minahasa Regency is a district that has land that has the potential for landslides because this area has high average rainfall, steep slopes (more than 40%), and is an earthquake-prone area. Areas prone to landslides and ground movements include areas around Suhuyon, Lowatag, Lomangi, Amburumalad, Maimbeng, Kaluya and Pangu. The research area is in Pangu Satu Village and its surroundings, East Ratahan District, Southeast Minahasa Regency, North Sulawesi Province. The method used in this research is the weighting and overlay scoring method. The results of this research are that the research area has 3 landslide susceptible zones, namely the zone with a low level of landslide vulnerability with an area of 0.01% of the area of the research area, the zone with a medium level of landslide vulnerability with an area of 98.1% of the area of the research area and the zone with a high level of landslide vulnerability with an area of 1.9% of the research area.